Identification of Students' Misconceptions using Four-Tier Diagnostic Assessment in Physics Learning Phase F - Agung Prastyo; Hanun Fithriyah; Alma Dias Rahmawati; Elvin Yusliana Ekawati (Universitas Tidar, 2024)
This research aims to identify students' misconceptions about momentum and impulse material using a four-tier diagnostic assessment instrument to implement learning evaluation in the Merdeka curriculum. This type of research is descriptive with a qualitative approach, with data collection techniques carried out through assessments and interviews. Interview data is used to reinforce assessment data. The instrument used in the study is a four-tier diagnostic test on momentum and impulse developed by the researchers. The results showed that 50% of students experienced misconceptions about momentum matter due to the assumption that if two objects move with the same kinetic energy should have the same speed so that the momentum of both objects can be determined by ignoring their velocity. Then, as many as 13. 9% of students experience misconceptions about the law of conservation of matter momentum because of students' assumptions that ignore direction on velocity vector quantities. In other physics concepts, some students are less careful in calculations. The results of this study are expected to be a reference for teachers in designing more meaningful Merdeka curriculum-based learning plans to help students better understand the concepts of momentum and impulse.